2020
DOI: 10.1155/2020/4647389
|View full text |Cite
|
Sign up to set email alerts
|

Equity in Health Care: A Qualitative Study with Refugees, Health Care Professionals, and Administrators in One Region in Germany

Abstract: Introduction. Equity in health is an essential issue and it would appear that it is not guaranteed for all human beings, especially refugee groups. The aim of this qualitative descriptive study was to explore the experiences of refugees, health care professionals, and administrators of refugee health care in a host country. Methods. The study used qualitative methods which consisted of a convenience sample of stakeholders directly and indirectly involved in care for refugees and refugees themselves. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Twenty-two studies reported results on health care access for refugees and asylum seekers, such as formal and bureaucratic barriers in reception countries [7][8][9][10][11][12][13], during flight [4,14], and the influence of length of stay and legal status on the use of health care services [7,8,[15][16][17][18]. Five studies [18][19][20][21][22] took into account the use of health care by groups under vulnerable conditions, such as refugees with mental illnesses.…”
Section: Descriptive Results On Utilisation and Access Barriersmentioning
confidence: 99%
“…Twenty-two studies reported results on health care access for refugees and asylum seekers, such as formal and bureaucratic barriers in reception countries [7][8][9][10][11][12][13], during flight [4,14], and the influence of length of stay and legal status on the use of health care services [7,8,[15][16][17][18]. Five studies [18][19][20][21][22] took into account the use of health care by groups under vulnerable conditions, such as refugees with mental illnesses.…”
Section: Descriptive Results On Utilisation and Access Barriersmentioning
confidence: 99%
“…In studies conducted with refugees in different countries, it is seen that the common problem is the language barrier for access to healthcare services [ 16 , 17 , 18 , 19 ]. In our study, the participants living in Şanlıurfa and Kilis stated that they sometimes had difficulty expressing themselves to healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The research question guiding the study is: What strategies do healthcare administrators use to retain their MHWs with more than 2 years of experience? For the purposes of this study, health care administrators (HCAs) were de ned as nonclinical professionals who make decisions related to the dayto-day administrative operations of health care facilities and hospitals and ensure adherence to healthcare laws and regulations (Guo, Berkshire, Fulton, & Hermanson, 2019;Hahn, Steinhäuser, & Goetz, 2020). Mental health workers were those who provide treatment, documents care, and meet the primary health care needs of patients with mental illness or behavioral problems (Herschell, Kolko, Hart, Brabson, & Gavin, 2020).…”
Section: Purpose Of the Studymentioning
confidence: 99%